Intranasal insulin for the treatment of alcohol use disorder: design and methodology of an alcohol interaction randomized controlled trial - Carolina L. Haass-Koffler; Bhavani Kashyap; Brian J. Gully; Sithara S. Nambiar; Rivkah Hornbacher; Stephanie L. Foster; Yuval Silberman; Robert M. Swift; Leah R. Hanson; William H. Frey, II (Contemporary Clinical Trials Communications)
Despite developments in treatments for alcohol use disorder (AUD), current pharmacotherapies face several limitations, including adverse events. Intranasal (IN) insulin has shown promise for addictive disorders. The overarching hypothesis of this trial is that by increasing brain cell energy and glucose metabolism, while reducing stress hormones, IN insulin may be an ideal approach for treating multiple domains of AUD including memory, executive function and impulsivity. Preclinical and clinical studies of IN insulin demonstrate that it is a safe and effective method for delivering insulin to the central nervous system, circumventing the blood brain barrier, and reducing adverse events associated with insulin use (hypoglycemia). The overarching goal of this Phase I/IIa, within-subject, crossover, double-blind, placebo-controlled, alcohol interaction trial is to test the IN insulin (80IU), compared to placebo (0.9 % saline) as a potential therapy for AUD. The primary aim assesses the safety and tolerability of IN insulin, compared to placebo, in individuals with AUD (N = 40) who are not currently seeking treatment. The secondary aim assesses the safety and tolerability of IN insulin, compared to placebo, when co-administered with alcohol (0.08 g/dL). Tertiary aims include assessing cognitive performance, memory, and impulsivity following IN insulin, or placebo, and alcohol administration. Finally, an alcohol cue reactivity procedure investigates the effect of IN insulin, compared to placebo, in alcohol craving. This is the first study to evaluate IN insulin in an AUD population and this manuscript describes the rationale, design, and methodology of the alcohol interaction trial. This study is designed to accelerate research for the development of novel medications to treat AUD and provide empirical evidence on the safety and efficacy of a neurotherapeutic approach to inform clinical practice. Clinical trial: NCT05988632. Fda/ind: 168417.